Identification of a target‐site mutation conferring resistance to triazine herbicides in oriental mustard (Sisymbrium orientale L.) from Australia. Issue 4 (17th October 2017) - Dang, Hue T.; Malone, Jenna M.; Boutsalis, Peter; Gill, Gurjeet; Preston, Christopher
Abstract : In southern Australia, oriental mustard ( Sisymbrium orientale ) has been controlled successfully by triazine herbicides for several decades. The screening of 40 populations that were collected from the southern grain belt of Australia during 2010 and 2013 for resistance to six different herbicides (glyphosate, diflufenican, imazamox, chlorsulfuron, atrazine and 2, 4‐dichlorophenoxyacetic acid) identified two oriental mustard populations as highly resistant to atrazine. Compared to the known oriental mustard‐susceptible populations (S1 and S2), these two resistant populations (P17 and P18) from near Horsham, Victoria, Australia, were 311‐ and 315‐fold resistant to atrazine, as determined by a comparison of the LD50 values. However, there was no resistance to diuron detected in these populations. Sequencing of the chloroplast psb A gene identified a missense mutation of serine 264 to glycine in both herbicide‐resistant oriental mustard populations, which is known to confer high‐level atrazine resistance in other species.